Dosimetric determination of tissue maximum ratios in small fields. Issue 3 (6th April 2018) - Shamsi, Qurat-ul-ain; Buzdar, Saeed Ahmad; Atiq, Atia; Atiq, Maria; Altaf, Saima; Iqbal, Khalid
Abstract: Aims: This exploration is intended to measure tissue maximum ratios (TMRs) in smaller fields through CC01 detector and to compare CC01 measured TMRs with Pinnacle treatment planning software (TPS) calculated TMRs. Materials and methods: CC01 compact chamber detector was used to measure TMR in water phantom for 6 and 18 MV beam delivered from Varian linear accelerator. Pinnacle TPS was employed in this study to calculate TMR from the measured percentage depth doses data. CC01 measured TMR data was compared with the calculated TMR data at depths from 5 to 20 cm for field sizes varying from 1 to 10 cm 2 . Results: For the smallest given field size of 1 cm 2, CCO1 measured 13·95% higher TMR value for 18 MV beam than that for 6 MV beam. At 20 cm depth for 1 cm 2 field size, TMR due to 18 MV beam was 52·4% higher than the TMR due to 6 MV beam. For 6 MV beam, the maximum difference appeared between the measured TMR and pinnacle calculated TMR was 2·8% and for 18 MV beam, the maximum difference was 4%. Conclusion: For both 6 and 18 MV beam, there was good agreement between CC01 measured and Pinnacle calculated TMRs for the field sizes ranging from 1 to 10 cm 2 . This exploration can be extended to the determination of other dosimetric parameters like TARs, TPRs in small fields.